Portal vein arterialization using an accessory right hepatic artery in liver transplantation. Issue 7 (3rd June 2013) - Paloyo, Siegfredo; Nishida, Seigo; Fan, Ji; Tekin, Akin; Selvaggi, Gennaro; Levi, David; Tzakis, Andreas
<x xml:space="preserve">Abstract</x> Portal vein thrombosis remains to be a challenging issue during liver transplantation even with the acquisition of innovative surgical techniques and years of experience. Most frequently, an initial eversion thromboendovenectomy is performed and depending on the extent of thrombosis and intraoperative findings, further revascularization options include venous jump grafts, portocaval hemitransposition, renoportal anastomosis or portal vein arterialization. Reports on these surgical approaches are limited although with acceptable outcomes. We present a 64‐year‐old patient with hepatitis C cirrhosis who underwent orthotopic liver transplantation with portal vein arterialization using an accessory right hepatic artery. Liver graft function has remained stable four years after transplant with notable aneurysmal dilatation of the portal vein. Liver Transpl 19:773–775, 2013. © 2013 AASLD.